The musical culture in the Persatuan Peranakan Cina Melaka / Rachel Ong Shu Ying - Rachel Ong, Shu Ying (2019)
This thesis examines how the Baba Nyonya community in Melaka represent their cultural identity through musical activities. The Baba Nyonya or Peranakan are longstanding culturally syncretic minority group, resulting from the marriage of southern-China Hokkien migrants and local women in the Straits Settlements. The result of the union is an eclectic material culture, custom and practices evident in Chinese, Malay, Dutch, British and Portuguese influences. As a case study, the focus of this research is the Persatuan Peranakan Cina Melaka (PPCM, Peranakan Chinese Association of Melaka). The association played an important role to safeguard the political standing of the Peranakan in the pre-WWII days. However, in the present, located in what was once considered Peranakan core area of Heeren Street, the association acts as a focal point for the congregation of Peranakan community in Melaka where cultural expression take place in the form of musical activities and performances and this is done through the three groups: BaNya choir group, The Melodians band, and Bunga Rampay dance group. The three groups share the same song repertoire, which is a collection of songs cultivated through family genealogies that evokes nostalgia and collective memory. Using participation-observation as a research method and frameworks like Turino’s (2008) participatory performance and Frith’s (1996) concept on music and identity, this study explores how popular music draws emotional alliances that invokes collective identity. Besides that, this thesis also deals with the notion of continuity and reinvention of tradition. It explores how the Peranakan song repertoire and performance practice reveal links to the past and its implications on the future. Negotiation of identity is a constant theme throughout this study, evident in the song repertoire and performances.